Capacity of High-Speed Powerline Communication in Vehicles - Hamdani, Deny; Safrianti, Ery (Makara Journal of Technology, 2003)
Powerline Communication (PLC) Systems intents to use the mains network in vehicles for high-speed data transmission. Carrier frequencies in the range of MHz are required to establish data rates of some megabits per second. In this paper, typical reference channels extracted from channel measurements are presented and computation results of their capacities according to Shannon’s theorem are presented. Furthermore, the effect of limitations of frequency range and power spectral density of transmitted signal on achievable capacity is investigated. This paper outlines an assessment for theoretical channel capacity and achievable data rates of vehicular PLC transmission schemes. Finally, EMC (Electromagnetics Compatibility) constraint according to CISPR 25 (Comite International Special des Perturbations Radioelectrique – The International Special Committee on Radio Interference) is deeply considered.